2014
DOI: 10.1111/1365-2656.12182
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in the relationship between performance and metabolic rate in wild juvenile Atlantic salmon

Abstract: Summary 1.Maintenance of metabolic rate (MR, the energy cost of self-maintenance) is linked to behavioural traits and fitness and varies substantially within populations. Despite having received much attention, the causes and consequences of this variation remain obscure. 2. Theoretically, such within-population variation in fitness-related traits can be maintained by environmental heterogeneity in selection patterns, but for MR, this has rarely been tested in nature. 3. Here, we experimentally test whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 74 publications
2
23
0
Order By: Relevance
“…These laboratory experiments, together with field studies showing spatial variation in the correlation between SMR and fitness measures (Álvarez & Nicieza ; Robertsen et al . ), support the hypothesis that variation in these metabolic traits may be maintained by environmental variation that favours different phenotypes in different habitats or at different times within and across years (Burton et al . ).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These laboratory experiments, together with field studies showing spatial variation in the correlation between SMR and fitness measures (Álvarez & Nicieza ; Robertsen et al . ), support the hypothesis that variation in these metabolic traits may be maintained by environmental variation that favours different phenotypes in different habitats or at different times within and across years (Burton et al . ).…”
Section: Discussionsupporting
confidence: 74%
“…Correlations between SMR and growth and survival in juvenile salmonid fishes ( S. salar and S. trutta ) have been found to be positive, negative or nonsignificant depending on which stream they are measured in, even when the genetic make‐up of individuals does not differ across streams (Álvarez & Nicieza ; Robertsen et al . ). These studies suggest that the fitness consequences of a given SMR are context‐dependent.…”
Section: Introductionmentioning
confidence: 97%
“…g . the natural environment) have found either negative or no correlations (Álvarez & Nicieza, ; Finstad et al , ; Norin & Malte, ; Robertsen et al , ). It has been suggested that the fitness advantages of a given SMR may thus depend upon the context (Burton et al , ), a hypothesis that is supported by recent stream‐tank experiments showing that SMR is positively correlated with growth rate when fishes are competing for access to a plentiful food supply but the relationship becomes negative once access to food is taken into account (Reid et al , , ).…”
Section: Individual Variation In Metabolismmentioning
confidence: 99%
“…Nevertheless, further research is needed to sort out the causal pathways involved in how thyroxine affects growth and associated activities. Although high growth rates often entail high metabolic rates (see below), this may not always be so: opposite associations have even been found (Medrano & Gall, 1976;Morgan & Iwama, 1991;Steyermark, 2002;Bayne, 2004;Álvarez & Nicieza, 2005;Careau et al, 2013;Robertsen et al, 2014). Therefore, rates of growth and metabolism can be uncoupled (see also Section III).…”
Section: (2) Cause Versus Effectmentioning
confidence: 99%